Mung Bean Starch-Derived Fermented Liquid Alleviates Constipation via 5-HT Modulation and Gut Microbiota Regulation: An In Vivo Study - Tao Ma; Mengtian Zhou; Xinru Zhang; Ruixue Zhang; Ying Wei; Jifeng Liu (Foods, 2025)
Background: Constipation is a common gastrointestinal disorder with a significant impact on quality of life. Methods: Constipation was induced in male ICR mice via 25% cotrimoxazole gavage (20 mL/kg/day for 7 days). Mice were divided into prevention (pre-MBSFL), treatment (MBSFL), and control groups. MBSFL was prepared by fermenting mung bean starch with Lactobacillus plantarum (1:3 w/v ratio, 37 °C for 48 h), and administered via daily oral gavage (250 mg/kg bw) for 14 days. Fecal parameters (water content and first black stool latency), gastrointestinal motility (gastric emptying and small intestinal propulsion), serum biomarkers (NO, VIP, SP, and 5-HT), and intestinal gene expression (5HTR4, SERT, and MAOA) were analyzed. Results: MBSFL intervention restored fecal water content by 38%, reduced first black stool latency from 6.2 h to 3.1 h, and improved small intestinal propulsion by 64%. Additionally, it downregulated serum NO (25%) and VIP (32%) while upregulating SP (49%) and 5-HT (78%) levels. Intestinal 5HTR4 and SERT expression increased by 78% and 71%, respectively, with MAOA suppression (25%). Microbial analysis revealed a 140% increase in Dubosiella and 49% in Lactobacillus abundance, alongside a 62% reduction in Mucispirillum. MBSFL contained polysaccharides (12.3% w/w) and organic acids, including hydroxy butyric acid (4.2 mg/mL). Conclusions: MBSFL alleviates constipation through dual mechanisms: modulating 5-HT pathway activity and restoring gut microbiota homeostasis.